DIVERSITY OF PLANT COMMUNITIES IN SECONDARY SUCCESSION OF IMPERATA GRASSLANDS IN SAMBOJA LESTARI, EAST KALIMANTAN, INDONESIA - Yassir, Ishak (Indonesian Journal of Forestry Research, 2014)
Regeneration of Imperata grassland areas is becoming increasingly important, both to create new secondary forest and to recover the original biodiversity. The diversity of plant communities in secondary succession of Imperata grasslands was studied using 45 subplots of 9 linear transects (10 m x 100 m). Data was collected and all stems over 10 cm dbh were identified, the Importance Values Index (IVI) for all trees were calculated, saplings and seedlings were counted and analysed, and soil samples were taken and analysed. Results showed that after more than 10 years of regeneration, 65 families were encountered consisting of 164 species, which were dominated by Vernonia arborea Buch.-Ham, Vitex pinnata L., Macaranga gigantea (Reichb.f. & Zoll.) Muell.Arg., Symplocos crassipes C.B. Clarke, Artocarpus odoratissimus Miq., and Bridelia glauca Blume. The effects of regeneration, from Imperata grassland to secondary forest, on soil were the strongest in the A-horizon where an increase in carbon, N content, and pH were observed. Our result shows that Imperata grasslands appear to be permanent because of frequent fires and human interferences and so far few efforts have been made to promote sustainable rehabilitation. If protected from fire and other disturbances, such as shifting cultivation, Imperata grassland will grow and develop into secondary forest.